An analysis on ethical climate and ethical judgment among public sector employees in Malaysia - Abdullah, Amalina; Sulong, Zunaidah; Mohd Said, Ridzwana (North American Business Press, 2014)
Many unethical business practices have alerted the deterioration of ethicalness among employees of public sector. As such, the public is skeptical towards the ethical issues in public sector and accuses them of forming unethical judgments. Specifically, this study aims to analyse the influence of ethical judgments on the intention towards unethical behavioural practices among employees in selected Malaysian public sectors. The data is analysed using a simple regression analysis based on 151 responses of a questionnaire survey. However, the overall finding of this study has shown a positive significant relationship between ethical climate and ethical judgment of employees’ behaviour on selected financial decisions in Malaysian public sectors. Hence, it will be useful to those in public sector in their effort to improve ethical awareness and ethical judgments. Recommendations are highlighted on how to improve the credibility and viability of public service delivery system towards national prosperity.